Survival rate of atraumatic restorative treatment: A systematic review - Mahammad Shareef Hajisaheb Kotyal; Nusrath Fareed; Hemanth Battur; Sanjeev Khanagar; Bhat Manohar; Rajeev Basapathy (Wolters Kluwer Medknow Publications, 2015)
Background: Atraumatic restorative treatment (ART) approach was developed in the mid-1980s to provide dental preventive and restorative care to underserved populations in areas that are out of reach. This method consists of the removal of infected (soft demineralized carious) tooth tissue with hand instruments only followed by restoring the cleaned cavity and associated pits and fissures with an adhesive restorative material. However, survival of ART restoration is a matter of intense speculation. Aim: To conduct a systematic review of the literature on the survival rate of ART restorations. Materials and Methods: A systematic search was carried out in MEDLINE, PubMed, and Cochrane databases from 1998 to 2014 using the term survival of ART in permanent teeth, primary teeth, ART restorative material. Results: The analysis of abstracts led to the selection of 36 studies. The research reports a survival rate of ART restoration for <2 years, 2-5 years, and >5 years ranging from 44.8% to 100%, 24.4% to 90%, and 72.6% to 86%. Survival of ART restoration is reported to be marginally higher in permanent molars compared to their primary counterparts. Conclusion: This systematic review revealed high survival rates for single-surface ART restorations in both primary and permanent molars. However, long-term clinical studies are scarce, and a level two and level three evidence was observed.